2014
DOI: 10.1111/cote.12117
|View full text |Cite
|
Sign up to set email alerts
|

Optimal yarn colour combination for full‐colour fabric design and mixed‐colour chromaticity coordinates based on CIE chromaticity diagram analysis

Abstract: It is challenging for textile designers to achieve full-colour effects in woven fabric using a limited set of coloured yarns. The common problems encountered during full-colour fabric design include an insufficient number of colours and a failure to match the fabric colour with the desired colour. Using the theories of primary colours and optical colour mixing, we examine the mixed-colour distribution of primary colour yarns on the basis of the CIE 1976 chromaticity diagram (CIE u 0 v 0 ). In our experiment, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
(21 reference statements)
1
7
0
Order By: Relevance
“…The pictures of fabrics (G2, G3 and G6) presented in Table 4 also demonstrate these changes. As indicated in the previous studies, there are linear or non-linear mathematical relationships between the mixed color attributes of fabric and the proportion of yarn color components on the fabric surface [7,13]. From Figures 2-5, it is easy to see that most combinations of red-blue and green-yellow have non-linear relationships between the mixed color attributes (a* and b*) of fabrics and the ratio of two yarn color components, for the surface color mixing of fabrics A (1-7), C (1-7), E (1-7) and G (1-7), while the a* value of fabric G (1-7) presents a linear relationship with the ratio of yellow to green components of yarns.…”
Section: Effect Of Proportion Of Colored Yarns On Mixed Color Attribumentioning
confidence: 91%
See 1 more Smart Citation
“…The pictures of fabrics (G2, G3 and G6) presented in Table 4 also demonstrate these changes. As indicated in the previous studies, there are linear or non-linear mathematical relationships between the mixed color attributes of fabric and the proportion of yarn color components on the fabric surface [7,13]. From Figures 2-5, it is easy to see that most combinations of red-blue and green-yellow have non-linear relationships between the mixed color attributes (a* and b*) of fabrics and the ratio of two yarn color components, for the surface color mixing of fabrics A (1-7), C (1-7), E (1-7) and G (1-7), while the a* value of fabric G (1-7) presents a linear relationship with the ratio of yellow to green components of yarns.…”
Section: Effect Of Proportion Of Colored Yarns On Mixed Color Attribumentioning
confidence: 91%
“…The three-dimensional color prediction models were further developed for single-and double-layered woven fabrics with the improved accuracy in lightness and chrome predictions [12]. Li et al investigated the four types of primary color combinations for full-color fabric design and mixed-color chromaticity coordinates based on CIE chromaticity diagram analysis [13]. They found that the RGBCMY (Red, Green, Blue, Cyan, Magenta, and Yellow) combination can create a relative complete and large color gamut.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] It is possible to establish a color prediction model for yarn-dyed fabric by exploring the color mixing rules of the interwoven warp and weft yarns. 21,22 However, most investigations on yarn-dyed fabrics focused on the color mixing effects and laws of the interwoven warp and weft yarns in different hues. Very few reports concerned the color evaluation of yarndyed fabrics interwoven with warp and weft yarns in the same hue but different color depths.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research was also performed by Li et al, who analysed four types of primary colour combination (six primary colour yarns: red—R, green—G, blue—B, cyan—C, magenta—M and yellow—Y) and eight weaves, and studied the colour gamut of different combinations in a CIE ultraviolet (UV) diagram. The results show that the RGBCMY combination offered a large colour gamut, which was not the case for the combinations RGB, CMY and RYBG.…”
Section: Introductionmentioning
confidence: 99%